Karikatur Karya G.M. Sudarta di Surat Kabar Kompas Kajian Pragmatik - Slamet Supriyadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2011)
Caricatures are used mainly to put forward constructive ideas on prevailing issues and to put forward humorous function. The types of speech act practiced are commisive, expressive, verdictive, assertive, directive, and performative. The dominating speech act found is directive. Based on the forms of speech act used, types of speech act practiced by the caricaturist are direct type of speech act. In the practice of cooperative principles, the caricaturist violates the maxims of quantity, quality, relevance, and manner. Politeness principles practiced by the caricaturist are tact, agreement, sympathy, and modesty maxims. Linguistic aspects utilized are phonological aspects, phrases, words, sentences, and discourse which coherence with the pictures.